2013
DOI: 10.1016/j.tsf.2013.04.037
|View full text |Cite
|
Sign up to set email alerts
|

Annealing effect of hybrid solar cells based on poly (3-hexylthiophene) and zinc-oxide nanostructures

Abstract: Motaung, D. et al. (2013). Annealing effect of hybrid solar cells based on poly (3-hexylthiophene) and zinc-oxide nanostructures. Thin Solid Films, Abstract:The structural growth and optical and photovoltaic properties of the organic-inorganic hybrid structures of zinc oxide (ZnO)-nanorods/poly-3-hexylthiophene (P3HT) and two variations of organic polymer blends of ZnO/ P3HT:C60 fullerene and ZnO/P3HT:6,6]-phenyl C61 butyric acid methyl ester were studied in detail during thermal annealing. The ordering of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…36 Already a lot of work has been performed on ZnO-based devices where many researchers replaced fullerenes completely by ZnO (synthesized ex situ or in situ, rod shaped or tetra-pod) as an electron acceptor without considerable signicant results being obtained. 37,38 Moreover, ZnO-graphene has been used as an electron acceptor with P3HT 39 reporting the PCE of 0.98% and also as a buffer layer in an inverted solar cell 33 with an enhanced efficiency of 4.15%. The novelty of our work lies on the surfactant-free synthesis of hydrophobic ZnO nanoparticles (and ZnO-graphene nanocomposite) for better charge transportation in polymer solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…36 Already a lot of work has been performed on ZnO-based devices where many researchers replaced fullerenes completely by ZnO (synthesized ex situ or in situ, rod shaped or tetra-pod) as an electron acceptor without considerable signicant results being obtained. 37,38 Moreover, ZnO-graphene has been used as an electron acceptor with P3HT 39 reporting the PCE of 0.98% and also as a buffer layer in an inverted solar cell 33 with an enhanced efficiency of 4.15%. The novelty of our work lies on the surfactant-free synthesis of hydrophobic ZnO nanoparticles (and ZnO-graphene nanocomposite) for better charge transportation in polymer solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the bumpy surface also scatters light away from the device. Previous studies reported that the rough surface reduces the efficiency of organic solar cells due to the formation of shunts . Since the resistance of the active layer is inversely related to the BHJ OPV mobility, and care should be taken in measuring mobilities due to a strong dependence on electric field , in order to further validate the effect of the additional electron acceptor (ZnO) on the P3HT:PCBM interface, the shunt resistance ( R Sh ) and series resistance ( R S ) of the solar cell were extracted from the slope of the J–V curves for inspection and are listed in Table .…”
Section: Resultsmentioning
confidence: 99%
“…These common solution processes generally produce CP ultrathin films with a low self-assembly degree and poor compactness, resulting in a very poor electrical performance. Annealing is a common posttreatment method for CP films to improve the crystalline structures. However, the strong interaction between the substrate and CP makes the molecular chains hardly diffuse in ultrathin films with a thickness less than 10 nm, resulting in annealing only minorly improving the microstructures of CP ultrathin films. In summary, modulating the microstructure of CP ultrathin films to reach a balance between crystalline and amorphous structures, which seems to be ideal for achieving both good mechanical and electrical properties, is difficult.…”
Section: Introductionmentioning
confidence: 99%